KEBUDAYAAN DAN PERADABAN - antasari, rina (Program Studi Muamalah Fakultas Syariah dan Hukum, 2016)
The word culture and civilization are two words that have enough understandingamong the experts, this is due to their different points of view in accordance with theexisting disciplines on them and see also the times. So for this time to approximately160 cultural understanding definitions found. Besides, there are those who equateCulture with the understanding between civilizations and there is also adistinguishing sense. And there is also known a few words related to Culture andCivilization in words Civilization, Culture, hadara, Tsaqafah and civilization.Therefore, in this article will explain what the similarities and differences in thesewords.